Top 7,000 & next 5,000 corporations business profiles 2000-2001. - Philippine Business Profiles and Perspectives, Inc. ([S.l] Philippine Business Profiles and Perspectives, Inc., 2000)
This CD-ROM contains a database of top 12,000 corporations from 1998 to 1999, list of industry standards and company profiles. Articles and past databases of top 12,000 corporations are also included.
Articles -- Database of top 12,000 '98-'99 -- List of industry classification '98-'99 -- Company profiles '98-'99 -- Historical database top 12,000 '97, '96, '95, '94.
System requirements: Pentium 133 Mhz or higher; 32MB RAM (64MB or higher recommended); Windows 95 & up; 12x CD-ROM drive; 640x480 resolution: 16 bit color or higher monitor.
Keywords: Corporations -- Philippines